The Gender and Educational Gradient in Fine Motor Skills among Older Adults : A Fixed Effects Growth Curve Model Approach - Hafeez, Samar (My University, 2026)
A substantial increase in life expectancy represents a major demographic shift in recent decades, making the quality of life of the growing elderly population an increasingly central topic. In this thesis, I assess the strength of older adults’ fine motor skills, which are needed for tasks like dressing, eating, or picking up small objects. Using longitudinal data from the Survey of Health, Ageing and Retirement in Europe (SHARE), this study explores how difficulties in fine motor skills change over time, and whether these patterns vary by sex and education among adults aged 50 and older. Using fixed-effects growth-curve models, I examine within-individual changes in fine motors over age and assess whether sex and education act as moderators of this relationship. The analyses draw on 145,970 individuals and 378,709 observations from SHARE waves 1–2 and 4–9. Overall, fine motor difficulties increase with age, particularly after age 70. The difference in age-related change by sex is small, with women showing a slightly steeper increase. Education, however, significantly moderates the age trajectories of men and women: individuals with higher levels of education experience a slower rise in fine motor difficulties than those with lower education, with the disparity most apparent at the lower end of the educational spectrum and among women. Additional control variables show that chronic disease is associated with higher difficulty scores, whereas more frequent physical activity is associated with lower difficulty scores.
Keywords: Keywords: Aging; fine motor skills; older adults; SHARE; fixed effects model; longitudinal analysis